Hydrological and ecological changes in western Europe between 3200 and 2000 years BP derived from lipid biomarker δD values in lake Meerfelder Maar sediments - Rach, Oliver; Engels, Stefan; Kahmen, A.; Brauer, Achim; Martín-Puertas, Celia; van Geel, Bas; Sachse, Dirk (Elsevier, 2017)
One of the most significant Late Holocene climate shifts occurred around 2800 years ago, when cooler and wetter climate conditions established in western Europe. This shift coincided with an abrupt change in regional atmospheric circulation between 2760 and 2560 cal years BP, which has been linked to a grand solar minimum with the same duration (the Homeric Minimum). We investigated the temporal sequence of hydroclimatic and vegetation changes across this interval of climatic change (Homeric climate oscillation) by using lipid biomarker stable hydrogen isotope ratios (δD values) and pollen assemblages from the annually-laminated sediment record from lake Meerfelder Maar (Germany).